PENGARUH LATIHAN KETAHANAN OTOT TUNGKAI TERHADAP KEMAMPUAN TENDANGAN LURUS PADA ATLET WUSHU SANDA CLUB UNPATTI - Elsijane P. Usmany; Albertus Fenanlampir; Mariana D. Hukubun (LPPM Universitas Cipta Mandiri, 2024)
Knowing the influence of lower limb muscle endurance training on the straight kicking ability of athletes in the Unpatti wushu sanda club, the research method used was field experimentation. It aimed to demonstrate whether there is a cause-and-effect relationship between lower limb muscle endurance training and the enhancement of straight kicking ability in Unpatti wushu sanda club athletes using circuit training method with a one-group pre-test post-test design. The population in the study consisted of all individuals who must have at least one similar trait, totaling 30 wushu sanda athletes. The sampling technique was purposive sampling, with the sample determined based on homogeneity, with 15 female wushu sanda athletes. The treatment instrument used in this study was the circuit training method. Meanwhile, the measurement instrument to determine straight kicking endurance used a 60-second test. The calculation results showed thitung = 6.243, while for ttabel = 1.76. Based on the critical region where H0 is rejected if the p value (sig.) <0.05, as thitung > ttabel, or 6.243 > 1.76. Therefore, it can be stated that the observational hypothesis or Ho is accepted, indicating the influence of lower limb muscle endurance training on straight kicking ability.